DO DIRECTORS AND TAX AGRESSIVENESS AFFECT FRAUDULENT FINANCIAL REPORTING? - wiralestari wiralestari (UNIB Press, 2019)
Tax is an obligatory financial contribution that individuals or institutions, as taxpayers, owe to the state without any direct benefits. It is compulsory and is collected under the regulation of law. The present study aims to examine the effectiveness of directors’ supervision and tax aggressiveness in diminishing frauds in financial reporting. The subject of this study is manufacturing companies listed in Indonesia Stock Exchange. The results of this study show that, firstly, effective directors’ supervision has significant correlation to diminishing fraudulent financial reporting. Directors, as the leaders of the company, demonstrated that they could perform their supervisory function very well. Secondly, tax aggressiveness has significant correlation to diminishing fraudulent financial reporting.